2020
DOI: 10.1080/01652176.2020.1781350
|View full text |Cite
|
Sign up to set email alerts
|

Some pathological observations on the naturally infected dromedary camels (Camelus dromedarius) with the Middle East respiratory syndrome coronavirus (MERS-CoV) in Saudi Arabia 2018–2019

Abstract: Some pathological observations on the naturally infected dromedary camels (Camelus dromedarius) with the Middle East respiratory syndrome coronavirus (MERS-CoV) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…We screened nasal swabs from 69 dromedary camels with real-time PCR to identify some active MERS-CoV animal shedders. The physical examination of these animals before slaughter showed no obvious clinical respiratory signs [ 22 ]. Despite some mild rhinorrhea in a limited number of animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened nasal swabs from 69 dromedary camels with real-time PCR to identify some active MERS-CoV animal shedders. The physical examination of these animals before slaughter showed no obvious clinical respiratory signs [ 22 ]. Despite some mild rhinorrhea in a limited number of animals.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported the normal structure of the respiratory tract in young and adult species of some animals, especially cattle, by the SEM; however, the histology of the respiratory tract of camels by SEM is still understudied. In a recent study, we showed some pathological alterations in the respiratory organs of three dromedary camels naturally infected with MERS-CoV by the H&E compared to two non-infected animals [ 22 ]. We first confirmed the detection of MERS-CoV-S and MERS-CoV-NC antigens in the tissues of these three animals by the IHC technique [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MERS-CoV is one of the most important zoonotic coronaviruses [1,2]. Dromedary camels remain the only known reservoir of this virus until now [1,6,10,13,23]. Although the virus was identified more than eight years ago, many aspects of the transmission cycle and molecular pathogenesis require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The nasal swabs were collected on a viral transport media, as previously described [ 10 , 23 ], the cotton swabs were introduced deeply into the nasal openings of the target animals toward the back of the nasal passage. Each cotton piece of swabs should be soaked with a considerable amount of the nasal secretions of the animal.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation